Metastasis to Paranasal Sinuses and Orbita of Breast Cancer With a Rare Metachronous Tumor of the Uterine Cervix - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
Breast cancer metastases are rarely seen in paranasal sinuses or orbit with a poor prognosis, and these cases were published as case reports. Moreover, metachronous tumors following breast cancer diagnosis are somewhat common, but uterine cervix is infrequent in them. In the present case, we report a 61-year-old female patient who had a biopsy-proven metastatic breast cancer to paranasal sinuses and orbita. She also had a cervical uterine cancer which is also unusually diagnosed following breast cancer. Palliative radiotherapy to paranasal sinuses (30 Gy) achieved a good response. However, she died due to leptomeningeal progression.
Keywords: Breast cancer; paranasal sinuses metastasis; radiotherapy; uterine cervix cancer; CARCINOMA; RADIOTHERAPY